2015
DOI: 10.1007/s00276-015-1578-5
|View full text |Cite
|
Sign up to set email alerts
|

Persistent trigeminal artery: a cross-sectional study based on over 3 years conventional angiography, CT angiography and MR angiography images

Abstract: PTA prevalence was similar to those previously reported, being commonly left-sided, Salas et al.'s lateral or petrosal type, Weon et al.'s type 3 and with no gender predominance. CVD and aneurysms incidence in the presence of a PTA were higher than in general population. Its anatomical relations make it essential to consider its presence and directional blood flow when planning endovascular and neurosurgical treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 24 publications
2
28
0
1
Order By: Relevance
“…This has been reported in many cases with hypoplasia in the BA proximal segments. 11 Despite these calibration differences in the PCoA, no significant changes in VA calibration, VA FV, and velocities were observed, which may indicate that the blood in the posterior circulation was largely used in the blood supply of the posterior fossa. A decrease in the flow rate may explain vertebrobasilar ischemia and presyncope.…”
Section: Discussionmentioning
confidence: 94%
“…This has been reported in many cases with hypoplasia in the BA proximal segments. 11 Despite these calibration differences in the PCoA, no significant changes in VA calibration, VA FV, and velocities were observed, which may indicate that the blood in the posterior circulation was largely used in the blood supply of the posterior fossa. A decrease in the flow rate may explain vertebrobasilar ischemia and presyncope.…”
Section: Discussionmentioning
confidence: 94%
“…Similar to the persistent PTA, the tentorial artery arises from the cavernous ICA directly and without branches. PTA is the most common variant of carotid-vertebrobasilar anastomoses, with an estimated prevalence of 0.1-0.6% [8]. While classic persistent PTA extends from ICA to the basilar artery, PTA variant continues as a cerebellar artery without basilar connection [9].…”
Section: Discussionmentioning
confidence: 99%
“…Among these 7 cases, there was a total of 28 aneurysms. Of these 28 aneurysms, 24 were treated with open surgery; 3 aneurysms were left untreated and followed with observation; 1 aneurysm was treated with interventional therapy. 7,[35][36][37][38][39][40] Because PPTA aneurysms are rare and there is a paucity of relevant research, the rupture risk of PPTA aneurysms remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…23 In addition, the incidence of PPTA with intracranial aneurysms has been reported to be 22% and 42% in two recent studies with a sample size of 2410 and 2488 cases, respectively. 24,25 The high incidence of PPTA with intracranial aneurysms in the two studies may be caused by the above-mentioned selection bias, and increased sample size may reduce the selection bias to some extent. In a study which included over 16,000 cases (the largest sample size reported in the literature as we know), magnetic resonance angiography was performed to analyse cases of PPTA.…”
Section: Relationship With Aneurysmmentioning
confidence: 97%